Coastal and River Embankment Performance at Cengkareng Drain Estuary Under Compound Hazards Conditions Using HEC-RAS 2D - Hastomo, Athena; Anggraheni, Evi; Prasetyo, Adi; Sutjiningsih, Dwita; Pratama, Mochamad Adhiraga; Umi Kalsum, Atina (Journal of the Civil Engineering Forum, 2023)
Jakarta is prone to pluvial, fluvial, and coastal flooding due to its geographical location and topography. In response to this problem, the Indonesian government has implemented several master plans, including the National Capital Integrated Coastal Development (NCICD). This ongoing program encompasses the construction of coastal and river embankment that stretch all over the coast of Jakarta. Since many coastal areas in Jakarta are residential or industrial, evaluating this performance of embankment has become crucial for effective flood management. The findings of this research can also support the development of other locations where NCICD embankment plan and enhance coastal resilience. Therefore, this research assessed the effectiveness of coastal and river embankment at Cengkareng Drain, a vital floodway in Jakarta, during extreme events that occur simultaneously. To simulate flooding events, two-dimensional HEC-RAS features were used to numerically calculate the area and depth of inundation. The simulation required geometry, terrain, land cover, and unsteady flow data. For the flow boundary conditions, a 100-year design rainfall, HHWL (Highest High Water Level), and 100-year design wave were considered to represent estuary conditions accurately. The simulation result showed that the maximum water level influenced by these factors was +3.145 mMSL, while the planned embankment top elevation was +3.40 mMSL. Furthermore, without the NCICD embankment, the simulation showed an inundation area of 1212.37 ha, which was reduced to 1111.22 ha after their implementation, leading to a decrease of 101.15 ha. This reduction significantly decreases potential damage to property and infrastructure, particularly in densely populated areas. The simulation also showed a reduction of 86.49 hectares or 66.22% in the inundation area with a depth exceeding 1 meter. These findings demonstrate the effectiveness of embankment in reducing the inundation area without any overtopping incidents.